Single Cell Determination of 7,8-dihydro-8-oxo-2′-deoxyguanosine by Fluorescence Techniques: Antibody vs. Avidin Labeling - Giusy Maraventano; Giulio Ticli; Ornella Cazzalini; Lucia A. Stivala; Mariella Ramos-Gonzalez; José-Luis Rodríguez; Ennio Prosperi (Molecules, 2023)
An important biomarker of oxidative damage in cellular DNA is the formation of 7,8-dihydro-8-oxo-2′-deoxyguanosine (8-oxodG). Although several methods are available for the biochemical analysis of this molecule, its determination at the single cell level may provide significant advantages when investigating the influence of cell heterogeneity and cell type in the DNA damage response. to. For this purpose, antibodies recognizing 8-oxodG are available; however, detection with the glycoprotein avidin has also been proposed because of a structural similarity between its natural ligand biotin and 8-oxodG. Whether the two procedures are equivalent in terms of reliability and sensitivity is not clear. In this study, we compared the immunofluorescence determination of 8-oxodG in cellular DNA using the monoclonal antibody N45.1 and labeling using avidin conjugated with the fluorochrome Alexa Fluor488 (AF488). Oxidative DNA damage was induced in different cell types by treatment with potassium bromate (KBrO3), a chemical inducer of reactive oxygen species (ROS). By using increasing concentrations of KBrO3, as well as different reaction conditions, our results indicate that the monoclonal antibody N45.1 provides a specificity of 8-oxodG labeling greater than that attained with avidin-AF488. These findings suggest that immunofluorescence techniques are best suited to the in situ analysis of 8-oxodG as a biomarker of oxidative DNA damage.